Maxillary sinus variation in hybrid macaques: implications for the genetic basis of craniofacial pneumatization. (June 2015) - Ito, Tsuyoshi; Kawamoto, Yoshi; Hamada, Yuzuru; Nishimura, Takeshi D.
Abstract : There has been a long‐standing debate regarding the diversification of paranasal sinuses, namely pneumatized spaces in the face. Functional adaptation and structural constraints have generally been suggested to explain sinus diversification in vertebrates. Here we investigated variation in the maxillary sinus and the external facial cranium in hybrid Taiwanese–Japanese macaques to estimate the genetic basis of phenotypic differences. The Taiwanese macaques have a large sinus, whereas the Japanese macaques have a small sinus; they are also significantly different in their external craniofacial morphology. Variations in the hybrids' external craniofacial morphology can be mostly explained by a simple additive model. In contrast, their sinus morphology significantly deviates from the value expected under this additive model, wherein most hybrids have a large sinus, similar to that in Taiwanese macaques, regardless of the degree of hybridization. When the whole structure is considered, a novel phenotype can be seen in the hybrids. Our results suggest that the sinus and face are independent of each other, both genetically and developmentally, and that the small sinus is mainly caused by intrinsic genetic factors, rather than being structurally constrained by the craniofacial architecture. Such genetic factors may have contributed to the enigmatic diversity of craniofacial pneumatization. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 115, 333–347.